Pengaruh Penerapan Presensi Sidik Jari (Finger Print) dan Motivasi Kerja Terhadap Peningkatan Kinerja Guru di SMAN 3 Kayuagung - Sani Noviani; Maulana Maulana; Alamsyah Alamsyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Sani Noviani. This study aims to: 1) determine the effect of the application of fingerprint attendance on the improvement of teacher performance of SMAN 3 Kayuagung, 2) determine the influence of work motivation on the improvement of teacher performance of SMAN 3 Kayuagung, and 3) determine the effect of the application of fingerprint attendance and work motivation on the improvement of teacher performance of SMAN 3 Kayuagung. The research method uses quantitative. This research was conducted in October – December 2020. The research population is 42 teachers taken with a total sampling technique. The data collection instrument uses a questionnaire. The results of the validity test of the variable of the application of fingerprint attendance ranged from 0.371-0.901, the variable of work motivation between 0.324-0.852, and the variable of teacher performance between 0.352-0.867. The reliability of the fingerprint attendance application questionnaire was 0.966, the work motivation questionnaire was 0.958, and the teacher performance questionnaire was 0.963. The analysis technique uses analysis prerequisite tests, regression analysis, t-tests, F tests, and determination coefficient tests. The results of the study were that: (1) there was a positive and significant influence between the variables of fingerprint attendance application and the improvement of teacher performance. This can be seen from the calculated T value (2.346) is greater than the T table (2.023) and the p-value is 0.000. (2) there was a positive but not significant effect between work motivation and teacher performance improvement. This can be seen from the T value of the calculation (1.943) is smaller than the T table (2.023) and the p-value is 0.000. (3) There is a positive and significant influence of the application of fingerprint attendance and work motivation on improving teacher performance. This can be seen from the value of F calculated (23.297) is greater than F table (3.238) and the regression equation obtained Y = 32.906+0.346X1+0.311X2+e, that variables X1 and X2 contribute by 54.4% to the variable Y. From the results of the determination coefficient of 54.4%. Another factor of 45.6% that affects the improvement of teacher performance was not discussed by the researchers.